Clinicoepidemiological Profile of Gram-negative Bacterial Sepsis (Carbapenem-resistant) in Pediatric Patients Aged 0–5 Years - Zubair A Naikoo; Mohd S Lone; Umar A Qureshi; Shafat A Tak (Pediatric Infectious Disease)
Aims and background: We investigated the clinicoepidemiological profile of gram-negative bacterial sepsis (carbapenem-resistant) in pediatric patients aged 0–5 years. Materials and methods: A total of 226 patients were recruited in the study. Comprehensive clinical, demographic data, and data on risk factors for gram-negative bacterial sepsis were collected. Data analysis primarily involved descriptive statistical methods. Results: The study cohort comprised mainly of male individuals (76.1%), primarily within the age-group of 0–1 month (64.4%). About 40% of patients presented with rapid breathing and refusal of feeds, followed by fever with cough (13.35%) and fever coupled with abnormal body movements (10.6%). 17.7% of patients received total parenteral nutrition (TPN), whereas 28.3% of patients required a central line. 18.1% of patients presented with cyanosis, 11.1% with icterus, and 4.9% with pallor. Leukopenia was seen in 87.2% of patients, and thrombocytopenia in 75%. C-reactive protein (CRP) was raised in 90%, and serum creatinine in 12.8%. Klebsiella pneumoniae (32.7%) was the most common organism isolated. 14.2% of the patients expired, with a mortality rate comparatively higher among patients with low-birth-weight (p-value < 0.001), patients experiencing longer hospital stays (p-value < 0.04), patients necessitating a central line (p-value < 0.001), and patients with increased serum creatinine levels (p-value < 0.001). Conclusion: This study provides insights into the epidemiology, clinical manifestations, and risk factors associated with sepsis due to carbapenem-resistant bacteria in patients aged 0–5 years and highlights the imperative need for stringent infection control measures and antimicrobial stewardship programs to improve sepsis outcomes in this population.